Pyrazoline analogues: Design, synthesis, and evaluation of anti-osteoporosis activity. (15th March 2022) - Sharma, Kriti; Kumar, Ashok; Prakash, Ravi; Tripathi, Alok; Singh, Rohit; Bajpai, Ranju; Sahasrabuddhe, Amogh A.; Singh, Divya; Narender, T.
Graphical abstract: Abstract: A series of pyrazoline compounds were synthesised and their osteogenic potential was explored. Out of fifteen, six compounds (3a, 4ac, 5aaa, 7, 8ab and 4aa ) showed significant osteoblast differentiation in the range of 1 pM –1 μM concentrations. Amongst all, compound 4aa was identified as most active molecule which showed effective mineralisation of osteoblast cells and up regulates the osteogenic marker gene such as Bmp-2, Runx-2 and Type-1col at both transcriptional and translational level. Besides exhibiting potential osteogenic activity, 4aa also possess significant anti-apoptotic activity at 1 pM &100 pM concentration and increases the osteoblast survival in serum deprived conditions.